Pemanfaatan Platform Moodle Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran PAI Di SMAIT Bina Bangsa Sejahtera Kota Bogor - Fatimah Azzahraa Anggawie; Budi Heryanto; Rumba Triana (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This study aims to find out student’s learning interest in Islamic religious education (IRE) lessons using moodle. In the world of education, the development of digital technology utilizes online based learning media that is more effective and interactive. Moodle is used to support the learning process in the form of attendance, assignment, quizzes and online material delivery. The use of this platform is expected to be able to create a more interesting learning atmosphere so that it can increase students' motivation and interest in learning in participating in IRE learning. The method used in this study is a qualitative method. In this study, the researcher collected data by conducting 3 stages, namely interviews, observations, and documentation. This interview was conducted with PAI teachers and students, observations were carried out directly at school to find out the IRE learning process and documentation was carried out by examining related documents. The results of this study show that the use of digital media such as e-learning, the moodle platform is able to increase students' motivation and interest in learning IRE subjects. The increase in students' interest in learning in using moodle in the IRE learning process has become more active and developed than before using the moodle platform website. This conclusion confirms that the use of the moodle platform in IRE learning is very useful and helps to increase students' interest and understanding of learning, as well as helping students to learn anywhere and anytime.